
13 May
2009
13 May
'09
8:32 a.m.
Lauri Alanko
On Tue, May 12, 2009 at 04:59:36PM -0400, Xiao-Yong Jin wrote:
f :: a -> b g :: (a -> b) -> c -> d
gf :: c -> d gf = g f
Now I want to handle exceptions in f and redefine f as in f'
f' :: a -> IO (Either e b)
So my question is how to define gf' now to use f' instead of f?
gf' :: c -> IO (Either e d)
Use Control.Monad.Error.ErrorT, it's exactly for this. You have to "monadize" g to be able to pass f' as an argument to it.
f' :: a -> ErrorT e IO b g' :: Monad m => (a -> m b) -> c -> m d gf' :: c -> ErrorT e IO d gf' = g' f'
So there is no way to do it without "monadize" g to g', is it? Big trouble, sigh. -- c/* __o/* <\ * (__ */\ <